Challenges and risks of using GLP-1 antagonists in treating type 2 diabetes and obesity - Głuszczyk, Agnieszka; Plizga, Jakub; Makłowicz, Aleksandra; Kopczyńska, Ewelina; Szpulak, Angelika; Frańczuk, Agata; Grzelka, Michalina; Głoskowska, Julia; Kuleta, Katarzyna; Karkos, Patrycja (Quality in Sport, 2024)
Introduction: Ozempic (semaglutide) is a long-acting GLP-1 receptor agonist widely used to treat type II diabetes and obesity. Its mechanism of action includes stimulation of insulin secretion, inhibition of glucagon secretion, and delaying gastric emptying, which leads to lower blood glucose levels and body weight reduction. Despite its therapeutic benefits, the use of Ozempic may cause side effects that affect patients' quality of life and their ability to continue treatment. This article aims to comprehensively analyze side effects associated with using Ozempic to provide a detailed understanding of their development mechanisms and their impact on patient's daily functioning.Material and Methods of Research: The literature was collected through searches in the PubMed and Google Scholar databases and references from the initially retrieved articles. Results: The literature review indicates various potential side effects of liraglutide, including gastrointestinal upset, pancreatitis, and the 'Ozempic face' phenomenon. This phenomenon, characterized by a skeletal facial appearance with deepened wrinkles, may result from the drug's impact on body composition and fat distribution, leading to a loss of subcutaneous fat in the face and a more pronounced appearance of underlying facial structures.Conclusion: Clinical studies highlight the need for continuous patient monitoring by healthcare providers to ensure the safe and effective use of Ozempic. Further education on a healthy lifestyle, diet, and physical activity is necessary to maintain the effects of drug therapy and prevent weight gain after treatment. Additional research on the long-term safety of GLP-1 is also crucial. Physicians should be aware of the potential risks and side effects associated with the use of Ozempic and should educate their patients to enable them to make informed decisions about their treatment.